2007
DOI: 10.1055/s-2006-955916
|View full text |Cite
|
Sign up to set email alerts
|

CASIROZ: Root Parameters and Types of Ectomycorrhiza of Young Beech Plants Exposed to Different Ozone and Light Regimes

Abstract: Tropospheric ozone (O(3)) triggers physiological changes in leaves that affect carbon source strength leading to decreased carbon allocation below-ground, thus affecting roots and root symbionts. The effects of O(3) depend on the maturity-related physiological state of the plant, therefore adult and young forest trees might react differently. To test the applicability of young beech plants for studying the effects of O(3) on forest trees and forest stands, beech seedlings were planted in containers and exposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…This was attributed to low irradiance and its effect on seedling carbohydrate status. Other studies examining shade intolerant deciduous species have found similar trends across light gradients in oak-hemlock and beech forests (Zeleznik et al, 2007;Turner et al, 2009). Mycorrhizal networks have been shown to play an important role in facilitating carbon transfer from overstory trees to understory seedlings experiencing light limitation (Beiler et al, 2009;Courty et al, 2010).…”
Section: Em Fungi and Forest Successionmentioning
confidence: 85%
“…This was attributed to low irradiance and its effect on seedling carbohydrate status. Other studies examining shade intolerant deciduous species have found similar trends across light gradients in oak-hemlock and beech forests (Zeleznik et al, 2007;Turner et al, 2009). Mycorrhizal networks have been shown to play an important role in facilitating carbon transfer from overstory trees to understory seedlings experiencing light limitation (Beiler et al, 2009;Courty et al, 2010).…”
Section: Em Fungi and Forest Successionmentioning
confidence: 85%
“…From each sample all roots were removed from soil and gently washed to remove all the remaining soil particles attached to the roots. For further processing, roots with diameter less than 2 mm (e. g., fine roots sensu Železnik et al, 2007, 2016) were selected and freeze dried at −92°C for 48 h. After freeze drying, roots were homogenized into a fine powder using a Retsch mixer mill (Retsch, Haan, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Hence, the outcome of this experiment reinforces branch-cuvette studies for adequate estimates of the O 3 sensitivity of tree foliage under field conditions. One needs to be aware, however, that assessment of whole-tree O 3 sensitivity must account, in addition, for belowground processes (Grebenc and Kraigher, 2007;Železnik et al, 2007) and root-shoot communication via phytohormonal signals (Winwood et al, 2007).…”
Section: Juvenile Trees and Branches As Surrogates Of Adult-tree O 3 mentioning
confidence: 99%